2021
DOI: 10.3390/foods10081678
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Green Method to Control Frauds of Geographical Origin in Traded Cuttlefish Using a Portable Infrared Reflective Instrument

Abstract: An appropriate seafood origin identification is essential for labelling regulation but also economic and ecological issues. Near infrared (NIRS) reflectance spectroscopy was employed to assess the origins of cuttlefish caught from five fishing FAO areas (Adriatic Sea, northeastern and eastern central Atlantic Oceans, and eastern Indian and western central Pacific Oceans). A total of 727 cuttlefishes of the family Sepiidae (Sepia officinalis and Sepiella inermis) were collected with a portable spectrophotometer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“… Zhang et al (2022b) distinguished the geographical origins of milk from five Chinese provinces by combining NIR with KNN, showing a discrimination rate of 98.67%. Curro et al (2021) used NIR to analyze the geographical origin of cuttlefish from five FAO (Adriatic Sea, northeastern and eastern central Atlantic Oceans, and eastern Indian and western central Pacific Oceans) fishing regions, with an accuracy reaching 92% after SVM algorithm analysis.…”
Section: Principle and Research Progress In Rapid Analysis Technologymentioning
confidence: 99%
“… Zhang et al (2022b) distinguished the geographical origins of milk from five Chinese provinces by combining NIR with KNN, showing a discrimination rate of 98.67%. Curro et al (2021) used NIR to analyze the geographical origin of cuttlefish from five FAO (Adriatic Sea, northeastern and eastern central Atlantic Oceans, and eastern Indian and western central Pacific Oceans) fishing regions, with an accuracy reaching 92% after SVM algorithm analysis.…”
Section: Principle and Research Progress In Rapid Analysis Technologymentioning
confidence: 99%
“… Yakes et al (2021) reported the analysis of two fish species and compared the performance of handheld NIR devices. Currò et al (2021) proposed handheld NIR instrument as a fast and green method to check the origin of cuttlefish. Yu et al (2020) assessed by rapid and nondestructive application of handeld NIRs the freshness of tilapia fillets.…”
Section: Applications To Food Quality Characterization and Adulterationsmentioning
confidence: 99%
“…For the unsupervised analysis, Principal Component Analysis (PCA) was employed as a descriptive tool to visualize the data distribution. On the other hand, the supervised approach involved utilizing Support Vector Machine (SVM), as reported in the works of Currò et al [8,14]. Concisely, the SVM model was developed using the 'caret' package, employing both the svmLinear and svmRadial kernels.…”
Section: Identification Species Modelmentioning
confidence: 99%